How do the employees of enterprises perceive the management paradigm? - Góralczyk Marzena (International Journal of Management and Economics)
The aim of this study is to show how the employees of enterprises perceive the management paradigm using the example of Penc’s approach, in relation to its individual aspects/components in the entities in which they are employed.